PENGGUNAAN KATO NAN AMPEK DI KALANGAN REMAJA JORONG BALAI SATU NAGARI PANINJAUAN, KECAMATAN X KOTO KABUPATEN TANAH DATAR - Rissa Monika Putri; Eva Fitrianti; Susanti Marisya (Ekasakti Educational Scientific Journal, 2025)
Kato nan ampek is a basis for how to speak to older people, to younger people, to mamak, datuak, in-laws, and in-laws, and also to peers. Not all teenagers in Jorong Balai Satu Nagari Paninjauan speak and behave in accordance with kato nan ampek. This research is a descriptive qualitative study describing the form and categorization of pronouns in the use of kato nan ampek among teenagers in Jorong Balai Satu Nagari Paninjauan. The instruments in this research were writing and recording equipment. The data in this study are pronouns in the use of kato nan ampek. Data were collected using note-taking and recording techniques. The results of this research show that in the use of pronouns in kato nan ampek, many teenagers still use pronouns that are not appropriate to their speech partners and there are still many teenagers who use words that are not in accordance with kato nan ampek. Pronouns that are still often used with older people are first person pronouns, the first person singular pronoun "den", the second person singular pronoun "kau/gau", and the third person singular pronoun "inyo/nyo". The pronouns that are often used with younger people are the first person singular pronoun "den" and the second person singular pronouns "you/gau" and "ang".